2017
DOI: 10.2139/ssrn.2901842
|View full text |Cite
|
Sign up to set email alerts
|

Child Age and Gender Differences in Food Security in a Low-Income Inner-City Population

Abstract: A long literature in economics studies differential allocations of resources to children within the family. In a study of approximately 1,600 very disadvantaged households with children in three cities in the U.S. from 1999 to 2005, significant differences in levels of food allocation, as measured by an indicator of food "insecurity," are found across children of different ages and genders. Using answers to unique survey questions for a specific child in the household, food insecurity levels are much higher am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Baker and Milligan (2016) found that parents spend more time in teaching activities for pre-school girls than boys. Durante et al (2015) conducted experiments in which people allocated more resources to daughters than sons, and Moffitt and Ribar (2016) found that disadvantaged families were more protective of daughters' food needs. Other things held equal, higher costs of daughters would reduce the amount of marriage-specific capital that a couple could produce and weaken the incentives to remain married.…”
Section: Theorymentioning
confidence: 99%
“…Baker and Milligan (2016) found that parents spend more time in teaching activities for pre-school girls than boys. Durante et al (2015) conducted experiments in which people allocated more resources to daughters than sons, and Moffitt and Ribar (2016) found that disadvantaged families were more protective of daughters' food needs. Other things held equal, higher costs of daughters would reduce the amount of marriage-specific capital that a couple could produce and weaken the incentives to remain married.…”
Section: Theorymentioning
confidence: 99%
“…Second, the 18-item household food security module does not provide the duration or frequency of food insecurity, because it only evaluates any occurrence of food-insecure events over the past 12 months. Third, this study assumed that the first child in a family was representative of all children in the family; however, older children in poor households may be more food insecure than younger children (Moffitt and Ribar, 2018). Finally, the present study is a cross-sectional research and, therefore, cause and effect relationships cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we do not see similar decreases in school lunch participation post‐SNAP pay for 5–10 year olds. This is an important finding, because middle and high school students are less likely to participate in school meals (Mitcherva and Powell ) and they are also less protected from food insecurity relative to younger children (Moffitt and Ribar ). Adolescents may have more attractive competing options or the stigma associated with subsidized lunches is higher for them, preferring to bring lunch from home or purchase from other vendors instead.…”
Section: Discussionmentioning
confidence: 99%